Sensorless nonlinear sliding mode control of the induction machine at very low speed using FM-MRAS observer - Mokhtar Touam; Mohammed Chenafa; Soufyane Chekroun; Ramzi‎ Salim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The induction motor is complex because its dynamic is nonlinear, multivariable and highly coupled. In addition, the induction motor (IM) controller design can be degraded due to wide ranges operating speed specially in low and near-zero speeds and also to variation of interval parameters such as the stator resistance change because of stator heating during operation. Our contribution is the use of a nonlinear sliding mode control using a fuzzy mutual reference adaptive system observer based on two fuzzy adaptation mechanisms to estimate both rotor speed and stator resistance. The proposed work was verified and compared by simulation and tested in various ranges of speed with motor and regenerating regions of operation. The results show that the proposed approach has proved good effectiveness in tracking and observation.